CHANGES THAT OCCUR IN THE BODY AS A RESULT OF EXCESSIVE DRINKING OF ENERGY DRINKS. (Ta'limning zamonaviy transformatsiyasi, 2025)
Mainly among young people, students and athletes between the ages of 15 and 35, there is a high interest in energy drinks. They are often resorting to energy a drinks with the aim of gaining instant energy. Comparison with other drinks: in the Uzbek market, energy drinks compete with breakfast drinks and carbonated drinks. Many consumers choose energy drinks as a source of caffeine.